Perception and Attitudes of Residents Towards Green Spaces in Croatia – an Exploratory Study - Marin, Ana Marija (Array, 2021)
Green spaces are important parts of urban infrastructure. COVID-19 pandemic and lockdown periods around the world have confirmed benefits that people derive from using green spaces for their physical and mental health. Green spaces need to meet the needs of users so that people can use them and benefit over time. It is important to consider users' perceptions and attitudes. User input proves beneficial in improving management practices. We investigated the differences in attitudes and perceptions of respondents from different large settlements in Croatia towards green spaces. Data on the use and perception of green spaces were collected in the first lockdown period in Europe and processed the part of the questionnaire on attitudes and perceptions towards green spaces. People have similar, mostly positive perceptions of green spaces regardless of the size of the settlement. Differences were found in the perception of disadvantages and needs related to the management of green spaces. This is the first study of the attitudes and perceptions on a large spatial scale in Croatia, so the results are exploratory and important. This study contributes to research on the social aspects of green spaces by investigating the influence of environmental context on perceptions and attitudes.